Accuracy of Prediction of Birth Weight by Fetal Ultrasound (Journal of KIST Medical College, 2020)
Introduction: Fetal weight estimation using ultrasonography (USG) is beneficial for the better feto-maternal outcome. This study was done to determine the accuracy of prediction of birth weight by fetal ultrasound.Methods: This was a cross-sectional study carried out in the Department of Radio diagnosis, Lumbini Medical College and Teaching Hospital (LMCTH), Palpa, Nepal from1st June to 31st December 2018.Fetal weight was calculated by USG in 325 women using Hadlock’s formula and correlated with birth weight.Results: Our study showed that fetal ultrasound using Hadlock’s formula has error in estimation of fetal weight by 189gm (SD: 111 gm). In 91.3% of the cases, there was an error of estimation by less than 10% compared to actual weight.Conclusion: It can be concluded that sonographic estimation of birth weight can be recommended to yield a better prediction of birth weight and to further evaluate fetal well-being.